2008
DOI: 10.3987/rev-07-621
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Synthesis Using Proline and Related Molecules. Part 2.

Abstract: -Organocatalytic asymmetric synthesis has been extensively studied and several important procedures for preparing optically active organic compounds have been developed. Research in this area has progressed rapidly in the last ten years. This review addresses the most significant advances in asymmetric synthesis using proline and related chiral organocatalysts mainly focusing on aldol reactions from the viewpoint of synthetic interests. This includes (1) proline-catalyzed aldol reactions, (2) proline-related c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(12 citation statements)
references
References 370 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…Such compounds are well-known organocatalysts. 29,34 The screening of different organocatalysts (Table 1) showed promising results in the reaction at room temperature. A comparative reaction without a catalyst resulted in 45% conversion after 96 h (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…Such compounds are well-known organocatalysts. 29,34 The screening of different organocatalysts (Table 1) showed promising results in the reaction at room temperature. A comparative reaction without a catalyst resulted in 45% conversion after 96 h (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…[41][42][43][44][45] In particular, proline is a remarkable candidate for the asymmetric reactions. [46][47][48][49][50] Amino acid with a carbonyl and an amino group can behave both as an acid and a base to facilitate chemical reactions. Jiang et al reported the synthesis of cyclic carbonates from CO 2 and epoxides catalyzed by amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…The use of proline derivatives as organocatalysts13 and as key building blocks of many pharmaceuticals and natural products14 ensures its status as a privileged structural motif. Chiral 2,3-dehydroproline (3-pyrroline) products commonly originate from natural 3-hydroxy proline,15 a neglected family of chiral proline products emerged as an ideal target for our new methodology.…”
mentioning
confidence: 99%